Single-Cell RNA Sequencing Integrated with Bulk-RNA Sequencing Analysis Reveals Prognostic Signatures Based on PANoptosis in Hepatocellular Carcinoma - Wang J; Yin X; Li Z; Liang P; Wang Y; Li X; Qiao W; Xiong C; Yu M; Ding X; Wang X (Journal of Hepatocellular Carcinoma)
Jiyin Wang,1– 5,* Xue Yin,1– 4,6,* Ziyi Li,1– 4,* Pu Liang,1– 4,* Yipeng Wang,1– 4 Xingling Li,1– 4 Wenying Qiao,1– 4 Chaoyang Xiong,1– 4 Minghang Yu,1– 4 Xiaoyan Ding,1– 4 Xi Wang1– 4,7 1National Key Laboratory of Intelligent Tracking and Forecasting for Infectious Diseases, Beijing Ditan Hospital, Capital Medical University, Beijing, People’s Republic of China; 2Beijing Key Laboratory of Viral Infectious Disease, Institute of Infectious Diseases, Beijing Ditan Hospital, Capital Medical University, Beijing, People’s Republic of China; 3Beijing Institute of Infectious Diseases, Beijing, People’s Republic of China; 4National Center for Infectious Diseases, Beijing Ditan Hospital, Capital Medical University, Beijing, People’s Republic of China; 5HBV Infection, Clinical Cure and Immunology Joint Laboratory for Clinical Medicine, Capital Medical University, Beijing, People’s Republic of China; 6Department of Infectious Disease, The Third Xiangya Hospital, Central South University, Changsha, Hunan, 410013, People’s Republic of China; 7Department of Oncology, Capital Medical University, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiaoyan Ding, National Key Laboratory of Intelligent Tracking and Forecasting for Infectious Diseases, Beijing Ditan Hospital, Capital Medical University, Beijing, People’s Republic of China, Tel/Fax +86-13811560276 ; +86-17316198975, Email dingxiaoyan198111@163.com Xi Wang, National Key Laboratory of Intelligent Tracking and Forecasting for Infectious Diseases, Beijing Ditan Hospital, Capital Medical University, Beijing, People’s Republic of China, Tel/Fax +86-13811560276 ; +86-17316198975, Email xiwang@ccmu.edu.cnPurpose: Drug resistance severely compromises therapeutic efficacy in hepatocellular carcinoma (HCC); however, the selection of precise treatment strategies for patients remains a critical unmet clinical need. This study investigated PANoptosis-related mechanisms underlying HCC progression to identify actionable therapeutic targets and optimize patient-specific treatment outcomes.Patients and Methods: Multi-omics analysis (single-cell/bulk RNA sequencing) combined with machine learning was used to identify the PANoptosis-related prognostic features. The association of PANoptosis-related expression with the tumor immune microenvironment and drugs was explored using bioinformatic analysis and experimental studies.Results: High PANoptosis risk exhibited immunosuppressive microenvironments and therapeutic resistance. The PANoptosis-related gene YIF1B has emerged as a dual prognostic biomarker and tumor driver that promotes proliferation, and is linked to immune dysfunction and drug resistance.Conclusion: YIF1B may be a promising therapeutic target. This PANoptosis framework bridges molecular mechanisms to clinical management, offering strategies for personalized HCC therapy and overcoming treatment resistance. Keywords: PANoptosis, hepatocellular carcinoma, YIF1B, drug resistant